2017
DOI: 10.3390/w9010046
|View full text |Cite
|
Sign up to set email alerts
|

UV-LEDs Efficiently Inactivate DNA and RNA Coliphages

Abstract: UV-LEDs are a new method of disinfecting drinking water. Some viruses are very resistant to UV and the efficiency of UV-LEDs to disinfect them needs to be studied. Drinking water was disinfected with UV-LEDs after spiking the water with MS2 and four UV-and/or Cl-resistant coliphages belonging to RNA or DNA coliphages isolated from municipal wastewater. UV-LEDs operating at a wavelength of 270 nm for 2 min with 120 mW of irradiation caused 0.93-2.73 Log 10 -reductions of coliphages tested in a reactor of a 5.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…According to the findings, quantifying reovirus infection could provide a useful index of enteric virus inactivation during full-scale treatment of wastewater ( Qiu et al, 2018 ). Furthermore, a previous study by Zyara et al (2017) reported that the efficacy of UV–LED inactivation of DNA and RNA coliphages separated from wastewater exhibited that a wavelength of 270 nm for 2 min induced a decrease of 0.93–2.73-log 10 in the coliphage test in a 5.2 L reactor, while a decrease of 4.30–5.16-log 10 improved with a 10 min irradiation time. The conventional mercury (Hg-UV) lamp, on the contrary, led to a reduction of 0.67–4.08-log 10 in 2 min and a reduction of 4.56–7.21-log 10 in 10 min at a wavelength of 254 nm in 10 mL of water.…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 89%
See 1 more Smart Citation
“…According to the findings, quantifying reovirus infection could provide a useful index of enteric virus inactivation during full-scale treatment of wastewater ( Qiu et al, 2018 ). Furthermore, a previous study by Zyara et al (2017) reported that the efficacy of UV–LED inactivation of DNA and RNA coliphages separated from wastewater exhibited that a wavelength of 270 nm for 2 min induced a decrease of 0.93–2.73-log 10 in the coliphage test in a 5.2 L reactor, while a decrease of 4.30–5.16-log 10 improved with a 10 min irradiation time. The conventional mercury (Hg-UV) lamp, on the contrary, led to a reduction of 0.67–4.08-log 10 in 2 min and a reduction of 4.56–7.21-log 10 in 10 min at a wavelength of 254 nm in 10 mL of water.…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 89%
“…The conventional mercury (Hg-UV) lamp, on the contrary, led to a reduction of 0.67–4.08-log 10 in 2 min and a reduction of 4.56–7.21-log 10 in 10 min at a wavelength of 254 nm in 10 mL of water. Hence, UV–light-emitting diode (LED) is a successful approach to disinfection of UV and Cl − resistant viruses ( Zyara et al, 2017 ). As a result, the optimal wavelength for UVB and UVC inactivation of microorganisms is 250 nm and 270 nm, respectively ( EPA, 1999b ).…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 99%
“…Since their emergence in early 2000, deep-ultraviolet (DUV) aluminum gallium nitride (AlGaN)-based light emitting diodes (LEDs) have gained significant attention owing to their wide range of applications, e.g., UV curing [ 1 ], medical diagnostics, phototherapy [ 2 ], optical sensing [ 3 , 4 ], security, communications [ 5 ], sterilization, and water and air purification [ 6 , 7 , 8 , 9 ]. However, despite the effort made to increase the external quantum efficiency (EQE) of UV LEDs, the reported values are still low, and barely reach a few percent in the UVC wavelength range, which is too low for commercial applications [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the III-nitride semiconductors are an important class of materials for devices emitting in the ultraviolet (UV) with applications, including UV curing, medical diagnostics, phototherapy, optical sensing, security, communications, sterilization, and water and air purification. These applications are made possible thanks to the widely tunable bandgap energy of AlGaN alloys ranging from 3.4 eV for GaN to 6.2 eV for AlN. The emission wavelength of AlGaN-based light-emitting diodes (LEDs) can cover the entire UV-A, UV-B, and UV-C spectral range.…”
mentioning
confidence: 99%